The Association between Vitamin D Deficiency and Fibrocystic Breast Disorder - Shabanian, Sheida; Rozbeh, Aliyeh; Mohammadi, Belgheis; Ahmadi, Ali; Arjmand, Mohammad-Hassan (Current Molecular Medicine, 2024)
Background: The role of deficiency of vitamin D in a wide range of human cancer, including breast cancer, has been proven, but its role in benign breast diseases remains unknown. This study aimed to determine the prevalence of vitamin D deficiency in patients with fibrocystic breast (FB) disease. Methods: First, the hospital prevalence of fibrocystic breast was determined by a crosssectional study. Then, patients were divided into two groups by a case-control study; women with confirmed fibrocystic breasts based on breast pain, physical examination, and ultrasonography were included as a case group (N=48), and age-matched women without fibrocystic breasts were also included as a control group (N=48). After recording the demographic and gynecological characteristics and exposure to the sun, gynecological records, and family history of fibrocystic breast, the blood sample was taken to determine vitamin D. Data were analyzed by Stata software. Results: The result indicated that the studied groups had significant differences in regards to weight, breast pain, the severity of breast pain, breast heaviness, family history of fibrocystic breast, history of breast disease, caffeine consumption, and exposure to sunlight (p <0.05), but did not show significant differences based on age, occupation, education, gynecological history, diabetes mellitus, hypertension, obesity and hypothyroidism, vegetable, fast food, and dairy products consumption. The frequency of vitamin D deficiency in the case group was 45.8%, and in the control group, it was 20.8%, and there was a statistically significant difference (p <0.05). Conclusion: Vitamin D deficiency is more common in women with fibrocystic breast disease and may play a role in the development of the disease.
Keywords: vitamin D deficiency